Artikel Review: Aktivitas Antibakteri dan Antioksidan Tanaman Baru Cina (Artemisia Vulgaris L.) - Suci Ainu Sella; Triyandi, Ramadhan; Afriyani, Afriyani; Iqbal, Muhammad (Medula, 2024)
Herbal medicines and their active ingredients have been a trusted source of treatment since ancient times. Herbal products with raw plant parts or bioactive compounds are increasingly in demand in the treatment of disease. Diseases caused by pathogenic bacteria have become an unresolved problem due to bacterial mutations that cause bacteria to be resistant to antibiotic agents. Long used as a medicinal plant, recent studies show that mugwort (Artemisia vulgaris L.) exhibits antioxidant, hypolipidemic, analgesic, antibacterial, antifungal, and hypotensive properties with chemical compounds such as flavonoids, sesquiterpene lactones, coumarins, acetylene, phenolic acids, organic acids, sterols, vitamins (ascorbic acid), monoterpenes, and sesquiterpenes. The content of mugwort (Artemisia vulgaris L.) can be used as a source of natural antioxidants, which can be used as ingredients for cosmetics, food supplements, and medicines. This plant can inhibit the growth of the bacteria Staphylococcus aureus, Bacillus subtilis, Klebsiella pneumoniae, Enterococcus sp., Propionibacterium acnes, and Staphylococcus epidermidis. From the literature, it is known that a 0.1% concentration of the test extract was able to inhibit bacterial growth, and a 5% concentration of methanol extract showed the best inhibition of bacterial growth with an inhibitory zone diameter of 24–25 mm. Plant antioxidant activity was tested using the DPPH method and the ORAC method. The best IC50 value was in the methanol extract, namely 4.3 µg/mL, with an ascorbic acid IC50 of 2.9 µg/mL. Meanwhile, the ORAC value was 5700 (µmol trolox EQ/g extract).